NATURAL BASES OF GENESIS OF UNTZUKUL ORNAMENTAL ART - G. G. GAZIMAGOMEDOV (Юг России: экология, развитие, 2015)
The work deals with Untzukul ornamental hatching wood by metal - it is the only phenomena in decoration applied art. Special attention is paid to succession of the traditions important for conservation and further development of the natural art trade of Daghestan republic.